The New Kid on the Block: HLA-C, a Key Regulator of Natural Killer Cells in Viral Immunity - Sarah Vollmers; Annabelle Lobermeyer; Christian Körner (Cells, 2021)
The human leukocyte antigen system (HLA) is a cluster of highly polymorphic genes essential for the proper function of the immune system, and it has been associated with a wide range of diseases. HLA class I molecules present intracellular host- and pathogen-derived peptides to effector cells of the immune system, inducing immune tolerance in healthy conditions or triggering effective immune responses in pathological situations. HLA-C is the most recently evolved HLA class I molecule, only present in humans and great apes. Differentiating from its older siblings, HLA-A and HLA-B, HLA-C exhibits distinctive features in its expression and interaction partners. HLA-C serves as a natural ligand for multiple members of the killer-cell immunoglobulin-like receptor (KIR) family, which are predominately expressed by natural killer (NK) cells. NK cells are crucial for the early control of viral infections and accumulating evidence indicates that interactions between HLA-C and its respective KIR receptors determine the outcome and progression of viral infections. In this review, we focus on the unique role of HLA-C in regulating NK cell functions and its consequences in the setting of viral infections.